Corporate Reputation Decoded : Building, Managing and Strategising for Corporate Excellence. - Kaul, Asha (SAGE Publications, 2014)
Corporate Reputation Decoded is the first book of its kind that traces the journey of Indian companies in building corporate reputation (CR). The book addresses CR in the Indian context and is in response to the growing interest of companies in this area. The book explains the process of building, maintaining and strategising for CR. It also discusses various aspects of CR-company's stakeholders, situations demanding CR interventions, and the impact of a com.